The Efficacy of palm oil mill effluent as a soil ameliorant - Jusop, Shamsuddin; Abdul Hamid, Sharifuddin (Universiti Putra Malaysia Press, 1995)
A field experiment was conducted to assess the effectiveness of palm oil mill effluent (POME) as a soil of ameliorant for the production of food crops. The POME was incorporated into the top 0-30 cm of Batang Merbau soil (Typic Kandiudult) prior to seeding with maize. Following maize, groundnut was grown. POME was applied at 0, 5, 10, 20, and 40 t ha-1, both in the presence and absence of 2 tdolomitic limestone ha-1. Exchhangeable Ca, Mg, and Al, pH (0.01 M CaCl2) in the topsoil prior to application of the treatments were 0.36, 0.19, 1.50 cmol kg-1. and 4.1, respectively. The average fresh cob yield of maize was 1.7 t ha-1, and did not increase with application of POME at rates of up to 10 t ha-1. Increasing the rate of POME to 20 and 40 t ha-1 resulted in fresh cob yield > 2.2 t ha-1. The increase in yield was attributed to improvement in the soil conditions for plant growth. Fresh cob yield in the presence of lime were > 2.2 t ha-1 at all rates of application of POME. Maize yield was significantly correlated with the exchangeable Al and Ca in the soil. Average pod yield for the first crop of groundnut was 3 t ha-1. Groundnut yield was not correlated with the exchangeable Al, Ca or Mg in the soil.